Música e saúde na escola - Karam, Joana Haar (2011)
The purpose of this work is to present the possibilities that the music offers to promote health and balance of social relations in a school environment. The research begins with the concepts` definition of music and music therapy, pointing their applications. Next, the difficulties faced by the school in the XXI century are discussed, then the contributions of music and music therapy, in order to change this scenario, are presented, showing the balance and stimulus of spirituality through the music. Finally, supported by the new legislation, that makes compulsory teaching of music at all levels of basic education, this is a new curricular propose that includes knowledge and skills development, aiming the full e continuing training of the students.